Characterization of the complete chloroplast genome of Pinus wangii (Pinaceae), an endangered and endemic species in China. Issue 2 (3rd July 2018) - Yang, Mei-Qing; Du, Yan; Ling, Li-Zhen
Abstract: The complete cp genome of Piuns wangii was 117, 014 bp in size, containing a large single copy (LSC, 64, 061 bp) region and a small single copy (SSC, 52, 007 bp) region separated by two reduced inverted repeats (IRs, 473 bp). A total of 107 genes were predicted, including 73 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Most of the 51 simple sequence repeats (SSRs) were mononucleotides motifs of A/T types and were found to be located in non-coding regions. Phylogenetic analysis of Asian Pinus showed P. wangii clustered a strongly-supported clade with Pinus morrisonicola, Pinus sibirica, Pinus wallichiana, and Pinus pumila .